High-strength, high-modulus and high-toughness shape memory poly (benzimidazole-benzoxazole) imide material with controllable photodegradability and preparation method thereof
The shape was solved by using imidazoles, oxazole aromatic heterocyclic diamines, biphenyl anhydrides and thixic acid, and the introduction of thixic acid as a photocontrol degradation group. The poor toughness and difficulty in degradation of memory polyimides have achieved the effect of controllable degradation under ultraviolet light irradiation and are suitable for a variety of high-tech fields.
Patent Information
- Application Number
- CN202411543004.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Shape memory polyimide has poor toughness, is easy to break after repeated bending, and is difficult to degrade, resulting in environmental pollution.
High-strength, high-mode, high-tough shape memory polyimides are prepared by imidazoles, oxazoles, aromatic heterocyclic diamines, biphendihydride and thixic acid. The polyimide is introduced into the polymer as a photocontrolled degradation group. , realize controlled light degradation.
The prepared polyimide has high strength, high modulus and high toughness, and can be controlled degraded under ultraviolet light, solving the problems of poor toughness and difficult degradation of materials. It is suitable for photodegradation, expandable flexible film capsules and Light-controlled degradation adaptive deformation flexible sensors and other fields.
Smart Images

Figure CN119431780A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multifunctional polymers, and in particular relates to a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability and a preparation method thereof. Background Art
[0002] Shape memory polymer (SMP) is a smart material that changes shape when the temperature is higher than the shape memory transition temperature (T trans ), the SMP is given a temporary shape under the action of external force, and the temperature is reduced to T trans After that, the temporary shape is fixed and when the temperature rises to T trans When the temperature is above 300 °C, SMP can return to its original shape autonomously. Compared with shape memory alloys and shape memory ceramics, SMP has the advantages of large deformation and light weight, and has broad application prospects in aerospace, flexible electronics, biomedical engineering and other fields. Shape memory polyimide has the advantages of high mechanical strength, high and low temperature resistance, and good thermal stability, but its toughness is poor and it is easy to break after repeated bending, causing material failure. In addition, because shape memory polyimide has rigid structures such as aromatic rings and aromatic heterocyclic rings, it is difficult to degrade after being discarded, causing environmental pollution.
[0003] Photodegradation is mainly a process of degradation by breaking the main chain of polymers using the action of light. Photodegradable materials can be divided into two types: the first is the additive type, in which photosensitizers are added to polymer materials. Through the action of light, the photosensitizers become active substances that can induce degradation of the main chain of polymers, thereby achieving the purpose of degradation. However, there is a risk of leakage of photosensitizers during use, which will cause pollution to the surrounding environment and limit their scope of use. The second is the synthetic type, in which photodegradable groups are introduced into the molecular structure of polymers to achieve the purpose of degradation. Photodegradable groups include o-nitrobenzyl ester derivatives, coumarin derivatives, Truxillic acid derivatives (truxilic acid), etc. During the photodegradation process, o-nitrobenzyl ester derivatives will release aldehyde or ketone byproducts, which will interact with proteins in the body and cause adverse reactions in the body. Coumarin derivatives have better biocompatibility and human safety than nitrobenzyl derivatives because their photodegradation products are alcohol hydroxyl and carboxyl groups, but the photodegradation time is 60-600 days, which is a long degradation time. In addition to the o-nitrobenzyl ester group and coumarin derivatives, truxilic acid is also a commonly used photodegradable group. Truxillic acid is a dimeric cyclic compound formed by a [2+2] cycloaddition reaction of two cinnamic acids. It can be used at a power of 500W / cm 2Under 265nm ultraviolet light irradiation, the [2+2] cyclic compound is broken down into two monomers. When the polymer chains are connected to the carboxyl groups on both sides, they can be broken down from the middle of the polymer, thereby breaking the main molecular chain, making the material brittle, and the plastic properties disappear. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of poor toughness and difficult degradation of shape memory polyimide, and to provide a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability and a preparation method thereof. The prepared shape memory polyimide has high strength, high modulus, high toughness, and can be controllably degraded under ultraviolet light.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A high-strength, high-modulus, high-toughness shape memory poly (benzimidazole-benzoxazole) imide material with controllable photodegradability, the molecular structure of the shape memory poly (benzimidazole-benzoxazole) imide material is as follows:
[0007]
[0008] Among them, the value range of n1+n2+n3 is 116-155.
[0009] Furthermore, the material is prepared from aromatic heterocyclic diamines, biphenyl dianhydride, and Truxillic acid derivatives; the aromatic heterocyclic diamines include imidazole aromatic heterocyclic diamines and oxazole aromatic heterocyclic diamines; the molar ratio of the imidazole aromatic heterocyclic diamines and oxazole aromatic heterocyclic diamines is 1:1; the Truxillic acid derivatives serve as light-controlled degradation groups; the molar ratio of the aromatic heterocyclic diamines, biphenyl dianhydride, and Truxillic acid derivatives is 2:1.7-1.88:0.12-0.3.
[0010] Furthermore, the imidazole aromatic heterocyclic diamine is one of 2-(4-aminophenyl)-5-aminobenzimidazole (DAPBI) and 2-(3-aminophenyl)-1H-benzimidazole-6-amine, the oxazole aromatic heterocyclic diamine is one of 2-(4-aminophenyl)-5-aminobenzoxazole (AAB), 2-(3-aminophenyl)-1,3-benzoxazole-5-amine and 2-(4-aminophenyl)-1,3-benzoxazole-6-amine, the biphenyl dianhydride is one of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 2,3,3',4'-biphenyltetracarboxylic dianhydride; the Truxillic acid derivative is tuximab. Synthesis route as shown in FIG. Figure 3 shown.
[0011] A method for preparing the above-mentioned high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability, the method comprising the following steps:
[0012] Step 1: dissolving an imidazole-containing aromatic heterocyclic diamine and an oxazole-containing aromatic heterocyclic diamine in a solvent to obtain an -NH 2 A mixed solution of groups;
[0013] Step 2: Under a protective atmosphere, add biphenyl anhydride to the -NH 2 The mixed solution of the groups was reacted for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0014] Step 3: Add tuximab to the -NH 2 A catalyst is added to the blocked polyamic acid solution and reacted for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0015] Step 4: pouring the polyamic acid solution containing the photosensitive group onto the substrate, placing it in a vacuum oven for vacuum drying to remove bubbles in the polyamic acid solution, and obtaining a polyamic acid solution substrate without bubbles;
[0016] Step 5: placing the polyamic acid solution substrate without bubbles in a high-temperature oven, and performing thermal imidization by gradually increasing the temperature to obtain a substrate containing a polyimide film;
[0017] Step 6: Place the substrate containing the polyimide film in water for 1-2 hours to complete demoulding. After drying, a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability is obtained.
[0018] Furthermore, in step 1, the solvent includes dimethyl sulfoxide.
[0019] Furthermore, in step 2, the protective atmosphere is nitrogen, and the reaction is carried out at room temperature.
[0020] Furthermore, in step three, the concentration of polyamic acid in the polyamic acid solution containing photosensitive groups is 17-22wt%, the catalyst is any one of dihydroxymethylacetone (DCC) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide) (EDC), and the catalyst content accounts for 5-10wt% of the mass of tuximab.
[0021] Preferably, biphenyl anhydride is added to the -NH 2The mixed solution of the photosensitive group is prepared by adding the photosensitive group to the polyamide acid solution, and the adding step is completed within 30 minutes. Under normal temperature conditions, in a nitrogen protection atmosphere, the reaction is carried out at a speed of 300r / min for 12 hours to obtain a polyamic acid solution. After that, thuja acid is added to continue the reaction for 24 hours, wherein the concentration of the polyamic acid containing the photosensitive group is 17wt%. The two-step reaction time of 12 hours and 24 hours respectively can ensure the performance of the obtained polyimide. If the time is too short, the molecular weight of the polyamic acid is low, and it is fragmented in the subsequent thermal imidization step, thereby causing many cracks, and ultimately leading to film failure. If the time is too long, the polyamic acid formed by polycondensation will be hydrolyzed, which will also cause a decrease in molecular weight, thereby affecting film forming properties.
[0022] Furthermore, in step 4, the vacuum drying treatment is specifically as follows: controlling the oven temperature to 60° C., maintaining it for 8 hours, and then raising the temperature to 100° C., maintaining it for 6 hours; and the substrate is a glass plate.
[0023] Furthermore, in step five, the gradient heating for thermal imidization is specifically as follows: the heating rate is 3°C / min, the temperature is increased to 150°C, and maintained for 2h; the heating rate is 3°C / min, the temperature is increased to 200°C, and maintained for 2h; the heating rate is 3°C / min, the temperature is increased to 250°C, and maintained for 2h; the heating rate is 3°C / min, the temperature is increased to 300°C, and maintained for 2h.
[0024] The above-mentioned high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability is applied in the fields of photodegradable deployable flexible film space capsules, controllable photodegradable adaptive deformation flexible sensors, etc. For example, the flexible film space capsule is in a compressed state before launch, which is beneficial to reduce the space size and weight and reduce the launch cost compared with the rigid metal space capsule; when performing a mission in space, the space capsule can actively unfold the structure when the temperature reaches above the SMPI glass transition temperature to avoid mechanical shock. After completing the mission, the film space capsule will be photodegraded under the ultraviolet radiation in space, thereby protecting the safety of the space environment and reducing space debris.
[0025] The beneficial effects of the present invention over the prior art are as follows: the present invention prepares a polyimide by using an aromatic heterocyclic diamine containing imidazoles and oxazoles, biphenyl dianhydride and tuximab, wherein the polyimide has a tensile strength of more than 250 MPa, a Young's modulus of more than 5 GPa, an elongation at break of more than 18%, a storage modulus of not less than 100 MPa in the shape recovery stage, and a glass transition temperature (T g ) exceeds 370℃, and has shape memory properties, with high shape fixation rate and shape recovery rate. Power 500W / cm 2After irradiation with 265nm ultraviolet light for 12-20h, the glass transition temperature and tensile strength are reduced, indicating that it has photodegradation characteristics. In addition, the prepared polyimide is an intrinsic photodegradable SMPI, which can solve the problems of uneven dispersion, easy precipitation and easy formation of stress concentration points of physically blended photosensitizers. The obtained polyimide has good photodegradation performance and has broad application prospects in the fields of photodegradable deployable flexible film space capsules, controllable photodegradable adaptive deformation flexible sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram showing the mechanism of the shape memory effect of the polyimide of the present invention;
[0027] Figure 2 is a flow chart of the preparation method of the present invention;
[0028] Figure 3 The synthetic route diagram of the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability of the present invention;
[0029] Figure 4 The stress-strain curve of the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability in Example 1 of the present invention;
[0030] Figure 5 The storage modulus and loss factor curve of the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability in Example 1 of the present invention;
[0031] Figure 6 The high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability in Example 1 of the present invention is subjected to a power of 500 W / cm 2 , loss factor curve after 265nm ultraviolet light irradiation for 12h;
[0032] Figure 7 The high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability in Example 1 of the present invention is subjected to a power of 500 W / cm 2 , stress-strain curve after 265nm ultraviolet light irradiation for 12h;
[0033] Figure 8 This is a diagram showing the thermally driven shape memory process of the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability in Example 1 of the present invention;
[0034] Fig. 9 Schematic diagram of the controllable photodegradation principle of SMPI. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0036] It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. The meanings of the terms "comprising", "including", "containing", and "having" are non-restrictive, that is, other steps and other components that do not affect the results can be added. The above terms cover the terms "consisting of..." and "consisting essentially of...". Unless otherwise specified, materials, equipment, and reagents are all commercially available. At the same time, it should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein.
[0037] The present invention regulates the molecular structure of polyimide monomers, and generates -NH 2 The polyamic acid is terminated with a group, and then tuximab containing a photosensitive group is added to the polyamic acid solution. The carboxyl reaction activity of tuximab is greater than that of the polyamic acid, so tuximab preferentially forms an amide bond with the amino group, which is equivalent to the chain extension reaction of the polyamic acid molecular chain segment. After thermal imidization, a multi-block shape memory poly (benzimidazole-benzoxazole) imide (SMPI) with a photodegradable group is obtained. The polymer has high strength, high modulus and high toughness, and the polymer has light-controlled degradation characteristics by controlling the proportion of chemical block photosensitive groups. It has broad application prospects in light-degradable deployable flexible film space capsules and controllable light-degradable adaptive deformation flexible sensors.
[0038] To achieve shape memory properties, the polymer molecular chain segment structure needs to have a reversible phase and a stationary phase. Poly(benzimidazole-benzoxazole)imide itself has an obvious glass transition, which can be used as a shape memory "switch". The stationary phase comes from the interaction between macromolecular chains, including macromolecular chain entanglement and π-π stacking; the reversible phase comes from the asymmetric imidazole ring molecular structure and oxazole ring molecular structure. Figure 1 As shown, when the temperature is lower than the glass transition temperature (T g ), the molecular chain segment motion is in a "frozen" state. When the temperature reaches T g After that, the free volume inside the material increases, the chain segment motion begins to "thaw", and a large deformation occurs under the action of external force. Maintaining this external force reduces the temperature to T gWhen the temperature is below T, the motion of the molecular chain segments is “frozen” again, and a temporary shape is obtained. In this process, the elastic strain energy stored is not released but stored in the polymer. g When the molecular chain segments obtain enough energy and free volume, they begin to move violently, the elastic strain energy stored inside is gradually released, and the material recovers from the temporary shape to its original shape on a macroscopic scale.
[0039] Example 1
[0040] (1) 2 mmol of 2-(4-aminophenyl)-5-aminobenzimidazole and 2 mmol of 2-(4-aminophenyl)-5-aminobenzoxazole were completely dissolved in 5.3 mL of dimethyl sulfoxide to obtain a 2 A mixed solution of groups;
[0041] (2) 3.76 mmol of 3,3',4,4'-biphenyltetracarboxylic anhydride was added into the -NH 2 The mixed solution of the group was added within 30 minutes. The reaction was carried out at room temperature, in a nitrogen atmosphere, at a speed of 300 r / min, for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0042] (3) 0.24 mmol of tuximab was added to the -NH 2 Add 0.08 mmol of catalyst dihydroxymethyl acetone to the blocked polyamic acid solution and react for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0043] (4) pouring the polyamic acid solution containing the photosensitive group onto a glass plate, placing it in a vacuum oven at 60° C. for 8 h; 100° C. for 6 h, evacuating the air to remove bubbles, and obtaining a polyamic acid glass plate without bubbles;
[0044] (5) placing the bubble-free polyamic acid glass plate in a high-temperature oven and performing thermal imidization by gradient heating, wherein the thermal imidization steps are as follows: heating at a rate of 3°C / min, heating to 150°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 200°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 250°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 300°C, and maintaining for 2 hours;
[0045] (6) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 2 h to complete demolding;
[0046] (7) The demolded film material is placed in an oven at 100° C. for 12 hours to evaporate the water, thereby obtaining a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole) imide with controllable photodegradation properties.
[0047] in, Figure 4 is a stress-strain curve diagram of the polyimide prepared in this embodiment; Figure 5 is a storage modulus and loss factor curve of the polyimide prepared in this embodiment; Figure 6 The polyimide prepared in this embodiment has a power of 500W / cm 2 , loss factor curve after 265nm ultraviolet light irradiation for 12h; Figure 7 The polyimide prepared in this embodiment has a power of 500W / cm 2 , stress-strain curve after 265nm ultraviolet light irradiation for 12h; Figure 8 This is a diagram demonstrating the shape memory process of the polyimide prepared in this embodiment.
[0048] from Figure 4 It can be seen that the tensile strength of the SMPI prepared in this embodiment at room temperature is 262.2MPa, the Young's modulus is 6.0GPa, and the elongation at break is 27.9%; Figure 5 It can be seen that the storage modulus of SMPI prepared in this embodiment is 6.7 GPa, T g is 380℃, that is, the shape memory transition temperature is 380℃, and the storage modulus in the shape recovery stage is as low as 100MPa; Figure 6 It can be seen that the SMPI obtained in this embodiment has a power of 500W / cm 2 , T after 265nm UV irradiation for 12h g is 352℃, which is higher than the original T g Reduce by 20℃; Figure 7 It can be seen that the SMPI obtained in this embodiment has a power of 500W / cm 2 The tensile strength after irradiation with 265nm ultraviolet light for 12h is 204MPa, which is 58.2MPa lower than the original tensile strength, indicating that the SMPI is photodegradable, and the decrease in molecular weight leads to a decrease in glass transition temperature and tensile strength; Figure 8 It can be seen that in a 390℃ thermal environment, an external force is applied to shape SMPI, and the temperature is lowered to room temperature. After the external force is removed, the temporary curved shape is still maintained. When heated to a 390℃ thermal environment again, SMPI can return to its original shape, with a shape fixation rate of 99% and a shape recovery rate of 98%. The polymer has light-controlled degradation properties by controlling the proportion of photosensitive groups in the chemical block, and is used in the fields of light-degradable deployable flexible film space capsules, controllable light-degradable adaptive deformation flexible sensors, etc.
[0049] Example 2
[0050] (1) 2 mmol of 2-(4-aminophenyl)-5-aminobenzimidazole and 2 mmol of 2-(4-aminophenyl)-5-aminobenzoxazole were completely dissolved in 5.3 mL of dimethyl sulfoxide to obtain a 2 A mixed solution of groups;
[0051] (2) 3.70 mmol of 3,3',4,4'-biphenyltetracarboxylic anhydride was added into the -NH 2 The mixed solution of the group was added within 30 minutes. The reaction was carried out at room temperature, in a nitrogen atmosphere, at a speed of 300 r / min, for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0052] (3) Add 0.3 mmol of tuximab to the -NH 2 Add 0.1 mmol of catalyst dihydroxymethyl acetone to the blocked polyamic acid solution and react for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0053] (4) pouring the polyamic acid solution containing the photosensitive group onto a glass plate, placing it in a vacuum oven at 60° C. for 8 h; 100° C. for 6 h, evacuating the air to remove bubbles, and obtaining a polyamic acid glass plate without bubbles;
[0054] (5) placing the bubble-free polyamic acid glass plate in a high-temperature oven and performing thermal imidization by gradient heating, wherein the thermal imidization steps are as follows: heating at a rate of 3°C / min, heating to 150°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 200°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 250°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 300°C, and maintaining for 2 hours;
[0055] (6) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 2 h to complete demolding;
[0056] (7) The demolded film material is placed in an oven at 100° C. for 12 hours to evaporate the water, thereby obtaining a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole) imide with controllable photodegradation properties.
[0057] The SMPI prepared in this embodiment has a tensile strength of 260 MPa, a Young's modulus of 5.8 GPa, and an elongation at break of 26.7%; a storage modulus of 6.4 GPa, and a T g The temperature is 379℃, the minimum storage modulus in the shape recovery stage is 110MPa; the passing power is 500W / cm 2, T after 265nm UV irradiation for 12h g The temperature is 348℃, the tensile strength is 196MPa, the shape fixity is 99%, and the shape recovery is 96%.
[0058] Example 3
[0059] (1) 2 mmol of 2-(4-aminophenyl)-5-aminobenzimidazole and 2 mmol of 2-(4-aminophenyl)-5-aminobenzoxazole were completely dissolved in 5.3 mL of dimethyl sulfoxide to obtain a 2 A mixed solution of groups;
[0060] (2) 3.66 mmol of 3,3',4,4'-biphenyltetracarboxylic anhydride was added into the -NH 2 The mixed solution of the group was added within 30 minutes. The reaction was carried out at room temperature, in a nitrogen atmosphere, at a speed of 300 r / min, for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0061] (3) 0.34 mmol of tuximab was added to the -NH 2 Add 0.11 mmol of catalyst dihydroxymethyl acetone to the blocked polyamic acid solution and react for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0062] (4) pouring the polyamic acid solution containing the photosensitive group onto a glass plate, placing it in a vacuum oven at 60° C. for 8 h; 100° C. for 6 h, evacuating the air to remove bubbles, and obtaining a polyamic acid glass plate without bubbles;
[0063] (5) placing the bubble-free polyamic acid glass plate in a high-temperature oven and performing thermal imidization by gradient heating, wherein the thermal imidization steps are as follows: heating at a rate of 3°C / min, heating to 150°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 200°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 250°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 300°C, and maintaining for 2 hours;
[0064] (6) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 2 h to complete demolding;
[0065] (7) The demolded film material is placed in an oven at 100° C. for 12 hours to evaporate the water, thereby obtaining a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole) imide with controllable photodegradation properties.
[0066] The SMPI prepared in this embodiment has a tensile strength of 258 MPa, a Young's modulus of 5.6 GPa, and an elongation at break of 24.8%; a storage modulus of 6.0 GPa, and a T g The temperature is 374℃, the minimum storage modulus in the shape recovery stage is 108MPa; the passing power is 500W / cm 2 , T after 265nm UV irradiation for 12h g The temperature is 343℃, the tensile strength is 186MPa, the shape fixity is 97%, and the shape recovery is 96%.
[0067] Example 4
[0068] (1) 3 mmol of 2-(4-aminophenyl)-5-aminobenzimidazole and 3 mmol of 2-(4-aminophenyl)-5-aminobenzoxazole were completely dissolved in 7.5 mL of dimethyl sulfoxide to obtain a 2 A mixed solution of groups;
[0069] (2) 5.61 mmol of 3,3',4,4'-biphenyltetracarboxylic anhydride was added into the -NH 2 The mixed solution of the group was added within 30 minutes. The reaction was carried out at room temperature, in a nitrogen atmosphere, at a speed of 300 r / min, for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0070] (3) 0.39 mmol of tuximab was added to the -NH 2 Add 0.13 mmol of catalyst dihydroxymethyl acetone to the blocked polyamic acid solution and react for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0071] (4) pouring the polyamic acid solution containing the photosensitive group onto a glass plate, placing it in a vacuum oven at 60° C. for 8 h; 100° C. for 6 h, evacuating the air to remove bubbles, and obtaining a polyamic acid glass plate without bubbles;
[0072] (5) placing the bubble-free polyamic acid glass plate in a high-temperature oven and performing thermal imidization by gradient heating, wherein the thermal imidization steps are as follows: heating at a rate of 3°C / min, heating to 150°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 200°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 250°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 300°C, and maintaining for 2 hours;
[0073] (6) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 2 h to complete demolding;
[0074] (7) The demolded film material is placed in an oven at 100° C. for 12 hours to evaporate the water, thereby obtaining a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole) imide with controllable photodegradation properties.
[0075] The SMPI prepared in this embodiment has a tensile strength of 261 MPa, a Young's modulus of 5.8 GPa, and an elongation at break of 25.8%; a storage modulus of 6.1 GPa, and a T g The temperature is 376℃, the minimum storage modulus in the shape recovery stage is 113MPa; the passing power is 500W / cm 2 , T after 265nm UV irradiation for 12h g The temperature is 345℃, the tensile strength is 190MPa, the shape fixity is 97%, and the shape recovery is 98%.
[0076] Example 5
[0077] (1) 3 mmol of 2-(4-aminophenyl)-5-aminobenzimidazole and 3 mmol of 2-(4-aminophenyl)-5-aminobenzoxazole were completely dissolved in 7.5 mL of dimethyl sulfoxide to obtain a 2 A mixed solution of groups;
[0078] (2) 5.55 mmol of 3,3',4,4'-biphenyltetracarboxylic anhydride was added into the -NH 2 The mixed solution of the group was added within 30 minutes. The reaction was carried out at room temperature, in a nitrogen atmosphere, at a speed of 300 r / min, for 12 hours to obtain -NH 2 A blocked polyamic acid solution;
[0079] (3) Add 0.45 mmol of tuximab to the -NH 2 Add 0.15 mmol of catalyst dihydroxymethyl acetone to the blocked polyamic acid solution and react for 24 hours to obtain a polyamic acid solution containing a photosensitive group;
[0080] (4) pouring the polyamic acid containing the photosensitive group onto a glass plate, placing it in a vacuum oven at 60° C. for 8 h; 100° C. for 6 h, evacuating the air to remove bubbles, and obtaining a polyamic acid solution glass plate without bubbles;
[0081] (5) placing the bubble-free polyamic acid glass plate in a high-temperature oven and performing thermal imidization by gradient heating, wherein the thermal imidization steps are as follows: heating at a rate of 3°C / min, heating to 150°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 200°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 250°C, and maintaining for 2 hours; heating at a rate of 3°C / min, heating to 300°C, and maintaining for 2 hours;
[0082] (6) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 2 h to complete demolding;
[0083] (7) The demolded film material is placed in an oven at 100° C. for 12 hours to evaporate the water, thereby obtaining a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole) imide with controllable photodegradation properties.
[0084] The SMPI prepared in this embodiment has a tensile strength of 255 MPa, a Young's modulus of 5.4 GPa, and an elongation at break of 23.6%; a storage modulus of 5.7 GPa, and a T g The temperature is 372℃, the minimum storage modulus in the shape recovery stage is 103MPa; the passing power is 500W / cm 2 , T after 265nm UV irradiation for 12h g The temperature is 340℃, the tensile strength is 174MPa, the shape fixity is 98%, and the shape recovery is 97%.
[0085] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications should all fall within the protection scope of the present invention.
Claims
1. A high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability, characterized in that: The molecular structure of the shape memory poly(benzimidazole-benzoxazole)imide material is shown below: Among them, the value range of n1+n2+n3 is 116-155.
2. The high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 1, characterized in that: The material is prepared from aromatic heterocyclic diamines, biphenyl dianhydride, and Truxillic acid derivatives; the aromatic heterocyclic diamines include imidazole aromatic heterocyclic diamines and oxazole aromatic heterocyclic diamines; the molar ratio of the imidazole aromatic heterocyclic diamines and the oxazole aromatic heterocyclic diamines is 1:1; the molar ratio of the aromatic heterocyclic diamines, biphenyl dianhydride, and Truxillic acid derivatives is 2:1.7-1.88:0.12-0.
3.
3. The high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 2, characterized in that: The imidazole aromatic heterocyclic diamine is one of 2-(4-aminophenyl)-5-aminobenzimidazole and 2-(3-aminophenyl)-1H-benzimidazole-6-amine; the oxazole aromatic heterocyclic diamine is one of 2-(4-aminophenyl)-5-aminobenzoxazole, 2-(3-aminophenyl)-1,3-benzoxazole-5-amine and 2-(4-aminophenyl)-1,3-benzoxazole-6-amine; the biphenyl dianhydride is one of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 2,3,3',4'-biphenyltetracarboxylic dianhydride; and the Truxillic acid derivative is tuximab.
4. A method for preparing the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1, dissolving an imidazole-containing aromatic heterocyclic diamine and an oxazole-containing aromatic heterocyclic diamine in a solvent to obtain a mixed solution containing -NH2 groups; Step 2: under a protective atmosphere, adding biphenyl dianhydride to the mixed solution containing -NH2 groups, reacting for 12 hours, and obtaining a -NH2-terminated polyamic acid solution; Step 3, adding tuximab to the -NH2-terminated polyamic acid solution, adding a catalyst, and reacting for 24 hours to obtain a polyamic acid solution containing a photosensitive group; Step 4: pouring the polyamic acid solution containing the photosensitive group onto the substrate, placing it in a vacuum oven for vacuum drying to remove bubbles in the polyamic acid solution, and obtaining a polyamic acid solution substrate without bubbles; Step 5: placing the polyamic acid solution substrate without bubbles in a high-temperature oven, and performing thermal imidization by gradually increasing the temperature to obtain a substrate containing a polyimide film; Step 6: Place the substrate containing the polyimide film in water for 1-2 hours to complete demoulding. After drying, a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability is obtained.
5. The method for preparing the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 4, characterized in that: In step 1, the solvent includes dimethyl sulfoxide.
6. The method for preparing the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 4, characterized in that: In step 2, the protective atmosphere is nitrogen, and the reaction is carried out at room temperature.
7. The method for preparing the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 4, characterized in that: In step three, the concentration of polyamic acid in the polyamic acid solution containing photosensitive groups is 17-22wt%, the catalyst is any one of dihydroxymethyl acetone and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide), and the catalyst content accounts for 5-10wt% of the mass of tuximab.
8. The method for preparing the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 4, characterized in that: In step 4, the vacuum drying treatment is specifically as follows: controlling the oven temperature to 60° C., maintaining it for 8 hours, and then raising the temperature to 100° C., maintaining it for 6 hours; the substrate is a glass plate.
9. The method for preparing a high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide material with controllable photodegradability according to claim 4, characterized in that: In step five, the gradient temperature increase for thermal imidization is specifically as follows: the temperature is increased to 150°C at a rate of 3°C / min, and maintained for 2h; the temperature is increased to 200°C at a rate of 3°C / min, and maintained for 2h; the temperature is increased to 250°C at a rate of 3°C / min, and maintained for 2h; the temperature is increased to 300°C at a rate of 3°C / min, and maintained for 2h.
10. An application of the high-strength, high-modulus, high-toughness shape memory poly(benzimidazole-benzoxazole)imide with controllable photodegradability as claimed in any one of claims 1 to 3 in the fields of photodegradable deployable flexible film space capsules, controllable photodegradable adaptive deformation flexible sensors, etc.
Citation Information
Patent Citations
Light-control nano-particle assembly and preparation method and application thereof
CN109453378A
Low-dielectric modified polyimide film and preparation method thereof
CN111825867A
Polyimide films and electronic devices
US20220340722A1